THE PLACE OF THE HIGH QUALIFICATIONS COMMISSION OF JUDGES AND THE HIGH COUNCIL OF JUSTICE IN THE ORGANIZATION OF ECONOMIC COURTS’ ACTIVITIES (Law and Safety, 2018)
The expediency of determining the role of the High Qualifications Commission of Judges and the High Council of Justice in the organization of the activity of general jurisdiction courts, in particular economic courts, has been substantiated. The author has conducted a comparative analysis of the updated legislation of Ukraine and the current Law “On the Judiciary and Status of Judges”; has revealed the novels in the legal statuses of the High Qualifications Commission of Judges and the High Council of Justice; has determined the role of these agencies in the organization of the activity of economic courts. The powers of the High Qualifications Commission of Judges and the High Council of Justice within the researched sphere have been differentiated.It has been argued that the main role of the High Qualifications Commission of Judges and the High Council of Justice in the organization of the activity of economic courts is to ensure the complete and timely deployment of these courts with a highly professional, competent and independent judiciary agency, ensuring compliance with the discipline, incompatibility and compliance with the requirements of the legislation while the administration of justice by the judges. At the same time, the main difference in the powers of these two agencies is that the High Qualifications Commission of Judges is the direct organizer and executor of the selection of personnel for positions of judges, carrying out a special verification for them, conducting a qualification evaluation, and on the basis of the results obtained during the implementation of these measures the High Council of Justice shall take the final decision on the appointment, dismissal, transfer, and disciplinary action of judges.